2005
DOI: 10.1063/1.1849426
|View full text |Cite
|
Sign up to set email alerts
|

Modeling room-temperature lasing spectra of 1.3-μm self-assembled InAs∕GaAs quantum-dot lasers: Homogeneous broadening of optical gain under current injection

Abstract: We studied the injection current dependence of room-temperature lasing spectra of a 1.3-μm self-assembled InAs∕GaAs quantum-dot laser both experimentally and theoretically. Starting from the ground-state lasing with a few longitudinal modes, the spectra showed splitting, broadening, excited-state lasing, and quenching of the ground-state lasing as the current increased. We could explain this unique current dependence by numerical simulation based on our quantum-dot laser theory, taking into account the inhomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 15 publications
4
87
0
Order By: Relevance
“…The impact of these two mechanisms on the operation of QD lasers has been addressed mostly on the theoretical side, with emphasis on the transition of nonequilibrium to quasiequilibrium carrier distributions [7][8][9][10] as well as the transition from broadband multimode lasing emission to a narrow lasing line. 7,[11][12][13] This paper presents a detailed experimental investigation of carrier processes in QD lasers around and above the lasing threshold. Fitting these results with a numerical model allows a quantitative estimation of the crucial material parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of these two mechanisms on the operation of QD lasers has been addressed mostly on the theoretical side, with emphasis on the transition of nonequilibrium to quasiequilibrium carrier distributions [7][8][9][10] as well as the transition from broadband multimode lasing emission to a narrow lasing line. 7,[11][12][13] This paper presents a detailed experimental investigation of carrier processes in QD lasers around and above the lasing threshold. Fitting these results with a numerical model allows a quantitative estimation of the crucial material parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As it is seen in Figure 1,a the GS band is split into two peaks (~1.254 and ~1.262 nm). According to M. Sugawara et al 5 this splitting can be attributed to the homogenous broadening of the QD optical transition. They also suggested that the GS lasing quenching at high currents could be explained by increase of the homogenous broadening.…”
Section: Quenching Of Gs Spectral Componentmentioning
confidence: 99%
“…It remains constant above the excited-state lasing threshold in some structures; 8,19 in others, the ground-state power approaches its maximum and then rollover occurs. 1,4,7,12,16,17 3. Internal and external differential quantum efficiencies For j th1 j < j th2 , the internal quantum efficiency can be introduced for ground-state lasing only [see Eq.…”
Section: Pinning Of Output Power and Necessary Condition For Ground-smentioning
confidence: 99%